Isolation of Piperin from The Fruit of Piper retrofractum - Iqbal Musthapa; Gun Gun Gumilar (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
This paper will described the isolation of major compound from MeOH extract from the fruit of Piper retrofractum. Using several chromatography technique including liquid vacuum chromatography and thin layer chromatography, and further purification using re-cristalization technique, Piperine, an alkaloids compound, was isolated from this extract. The structure of this compound was determined using spectroscopic methods including FTIR, 1D-NMR and 2-D NMR.Keywords : P.retrofractum, alkaloids, piperine, structure elucidation